Large Outcomes Trials are Crucial for Understanding Diabetes - Vinall, Maria (MD Conference Express, 2014)
Large outcomes trials are crucial to the understanding of how best to treat patients with diabetes, and the results from meta-analyses, administrative databases, and epidemiologic data from small trials are no replacement. While the data from these trials are useful in that they can be used to identify risk factors, the relationship between risk factors and outcomes is not always clear.